Hemostasis and thrombosis - DeLoughery, Thomas G. (Springer International Publishing : Imprint: Springer, 2015)
Since the second edition of Hemostasis and Thrombosis published over a decade ago, advances on assessing, treating and preventing common and rare hemostatic problems have emerged.  This latest edition features these new developments while providing practical information on diagnosing and managing these troublesome conditions often found in clinical practice.  Concise and convenient, healthcare professionals will find this text to be an invaluable resource.